Attitude and Political Ideology of 2024 Indonesian Presidential Candidates Reported in Jakartapost.com - Thahara, Yopi; Firdaus, Ahmad Yusuf; Amelia, Firqo; Lailiyah, Sufil; Novitasari, Nine Febrie; Mila, Dwi Taurina; Khissoga, Rahajeng Hauwwa (UIN Salatiga, 2024)
This research examines the evaluation of attitudes in 5 articles from Jakartapost.com regarding the electoral debate of presidential candidates. As a mass media outlet targeting readers both domestically and internationally, Jakartapost.com is required to maintain neutrality in reporting on presidential debates. Therefore, the research aims to understand the attitudes and political ideology of 2024 Indonesian presidential candidates reported by Jakartapost.com. The news was analyzed using the appraisal system proposed by Martin and White (2005), categorizing attitudes into affect, judgment, and appreciation. This research utilized qualitative methods with embedded case study and Spradley’s analysis to identify cultural patterns and themes within the data. The results showed that attitudes consisted of 39.7% negative and 24.6% positive judgments, 16.4% negative and 8.2% positive appreciations, and 9.6% negative and 1.4% positive affects. The appraisal system can identify political ideologies of the three presidential candidates. Anis Baswedan and Ganjar Pranowo express conflicting attitudes towards the current government, indicating their role as opposition and socialist populism, while Prabowo Subianto aligns himself with the current government known as technocratic populism. Journalists tend to assess Prabowo more positively compared to other candidates, suggesting a bias towards supporting him in the 2024 election.